An exploratory study of cultural understanding in English as a foreign language reading in Argentina - Porto, Melina (2011)
The general aim of this study is to describe and comprehend how the specific population investigated in this context, college students at Universidad Nacional de La Plata in Argentina, comprehended the cultural content of literary narrative texts in EFL reading.